Behavioral pharmacology of drug abuse : current status - Li, Jun-Xu (Advances in pharmacology, 2022)
Behavioral Pharmacology of Drug Abuse: Current Status, Volume 93 provides an update on our current understanding of animal and human behavioral pharmacology in major classes of drugs of abuse, including nicotine, alcohol, opioids, psychostimulants, and hallucinogens, drug-environment interactions, neurochemical mechanisms and medications developments. This volume updates the field of behavioral pharmacology based on new knowledge gained in the past decade.